Pengaruh Kecerdasan Emosional Terhadap Penyesuaian Sosial Siswa Kelas XI Di SMA N 2 Rembang - Swandana Adi Saputra; Venty Venty; Siti Fitriana (Universitas Muhammadiyah Metro, 2026)
Social adjustment is an important ability that students need to establish harmonious relationships within the school and community environment. One factor that is assumed to influence social adjustment is emotional intelligence. This study aimed to determine the effect of emotional intelligence on the social adjustment of eleventh-grade students at SMA Negeri 2 Rembang. The study employed a quantitative approach with a simple linear regression design. The population consisted of 224 students, while 139 students were selected as the sample using purposive sampling techniques. Data were collected through Likert-scale questionnaires measuring emotional intelligence and social adjustment. Data analysis was conducted using IBM SPSS version 22 through normality testing, linearity testing, and simple linear regression analysis. The results showed that the data were normally distributed with a significance value of 0.074 (> 0.05), and the relationship between variables was linear with a deviation from linearity significance value of 0.700 (> 0.05). Regression analysis revealed an F value of 28.456 with a significance level of 0.000 (< 0.05), while the hypothesis test showed a t value of 5.754 with a significance level of 0.000 (< 0.05). The findings indicated that emotional intelligence had a positive and significant effect on students’ social adjustment. The higher the students’ emotional intelligence, the better their social adjustment ability. These findings highlight the importance of developing emotional intelligence to improve students’ social adjustment in the school environment.